Environmental impacts of different crop rotations in terms of soil compaction. (1st October 2016) - Götze, Philipp; Rücknagel, Jan; Jacobs, Anna; Märländer, Bernward; Koch, Heinz-Josef; Christen, Olaf
Abstract: Avoiding soil compaction caused by agricultural management is a key aim of sustainable land management, and the soil compaction risk should be considered when assessing the environmental impacts of land use systems. Therefore this project compares different crop rotations in terms of soil structure and the soil compaction risk. It is based on a field trial in Germany, in which the crop rotations (i) silage maize (SM) monoculture, (ii) catch crop mustard (Mu)_sugar beet (SB)-winter wheat (WW)-WW, (iii) Mu_SM-WW-WW and (iv) SB-WW-Mu_SM are established since 2010. Based on the cultivation dates, the operation specific soil compaction risks and the soil compaction risk of the entire crop rotations are modelled at two soil depths (20 and 35 cm). To this end, based on assumptions of the equipment currently used in practice by a model farm, two scenarios are modelled (100 and 50% hopper load for SB and WW harvest). In addition, after one complete rotation, in 2013 and in 2014, the physical soil parameters saturated hydraulic conductivity (kS ) and air capacity (AC) were determined at soil depths 2–8, 12–18, 22–28 and 32–38 cm in order to quantify the soil structure. At both soil depths, the modelled soil compaction risks for the crop rotations including SB (Mu_SB-WW-WW, SB-WW-Mu_SM) are higher (20 cm: medium to very high risks; 35 cm: no to medium risks) than for those without SB (SM monoculture, Mu_SM-WW-WW; 20 cm: medium risks; 35 cm: no to low risks). This increased soil compaction risk is largely influenced by the SB harvest in years where soil water content is high. Halving the hopper load and adjusting the tyre inflation pressure reduces the soil compaction risk for the crop rotation as a whole. Under these conditions, there are no to low soil compaction risks for all variants in the subsoil (soil depth 35 cm). Soil structure is mainly influenced in the topsoil (2–8 cm) related to the cultivation of Mu as a catch crop and WW as a preceding crop. Concerning kS, Mu_SB-WW-WW (240 cm d −1 ) and Mu_SM-WW-WW (196 cm d −1 ) displayed significantly higher values than the SM monoculture (67 cm d −1 ), indicating better structural stability and infiltration capacity. At other soil depths, and for the parameter AC, there are no systematic differences in soil structure between the variants. Under the circumstances described, all crop rotations investigated are not associated with environmental impacts caused by soil compaction. Highlights: Soil compaction risk was modelled for entire crop rotations on farm scale. Crop rotations with sugar beet and/or silage maize were tested for soil structure. Crop rotations caused medium to very high risks for the topsoil. Risks were low for the subsoil when reducing hopper load/tyre inflation pressure. Differences in soil structure were not related to sugar beet or silage maize cropping.